CAP 2013 reform: consistency between agricultural challenges and measures - Popp, József; Pető, Károly; Jámbor, Attila (Applied Studies in Agribusiness and Commerce, 2015)
The latest reform of the Common Agricultural Policy has just been accepted, identifying important challenges for EU agriculture but proposing only limited changes to the previous CAP. Now it is time for the implementation of the new measures. However, from a theoretical point of view, it seems that the CAP can hardly meet the challenges it faces due to the inconsistencies between the predefined challenges and the measures proposed to meet them. The aim of the paper is to analyse the consistency between the challenges of European agriculture and the policy measures aimed at meeting them. It seems that not all measures are consistent with the challenges.